Key events in the process of sex determination and differentiation in early chicken embryos - Xiaoqian Lv; Changhua Sun; Xin Liu; Guanzheng Liu; Wei Gong; Hongwu Qian; Zeyu Li; Jun Wu; Xilin Zhu; Jiuzhou Song; Yingjie Niu; Hongyan Sun; et al. (Animal Bioscience)
Objective Current understanding of sex determination and differentiation mechanisms during early chicken embryonic development remains incomplete. To address this, we applied RNA sequencing to identify male-female expression differences at critical developmental stages (E0 blastocysts, E3.5-E6.5 genital ridges, E18.5 gonads), focusing on glycolysis, histone acetylation, and DNA methylation. This approach aims to unravel key regulatory mechanisms and advance developmental biology insights. Methods We analyzed molecular mechanisms of chicken sex determination at key stages (E0 blastocysts, E3.5-E6.5 genital ridges, E18.5 gonads) using RNA sequencing. Glycolysis, histone acetylation, and DNA methylation levels were assessed in embryonic stem cells and chicken embryonic fibroblasts. E18.5 gonads were treated with glycolytic activators (SB431542 and PD0325901 [2i]), a DNA demethylation activator (Vitamin C [Vc]), or an inhibitors of histone acetylation modification (valproic acid [VPA]). Sex-related gene expression, hormone levels, and gonad morphology were evaluated to determine treatment effects. Results Key findings revealed that sex differences emerged as early as the blastocyst stage, intensified with embryonic development and were marked by a surge in sexually dimorphic gene expression. Gene Ontology and Kyoto encyclopedia of genes and genomes analyses highlighted the pivotal roles of energy metabolism and epigenetic modification process during this critical period. 2i, VC, or VPA interventions targeting E18.5 embryo gonads, induced a remarkable transformation of ovarian tissue into a testis-like structure, characterized by cortical thinning, medulla densification, downregulation of female-specific genes (FOXL2, WNT4), upregulation of male-specific genes (SOX9, AMH), and increased testosterone secretion. This phenotypic and molecular shift underscores the ability of metabolic and epigenetic modulators to reprogram ovarian development towards a male-like pattern, preserving male sexual characteristics. Conclusion Our study establishes energy metabolism and epigenetic regulation as central drivers of avian sex determination. These findings advance understanding of vertebrate developmental biology and provide a framework for dissecting regulatory networks in avian sexual development.